2017
DOI: 10.7124/bc.00094b
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic activity of novel thiazole derivatives

Abstract: The development of novel efficient substances for anticancer chemotherapy is an important problem of medicinal chemistry. Aim. To evaluate the level of cytotoxic action of novel thiazole derivatives towards tumor cell lines of different origin. Methods. Four N acylated 2-amino-5-benzyl-1,3-thiazoles (5a-d) were synthesized by reaction of 2-amino-5-R-benzyl-1,3-thiazoles with acid chlorides in the presence of triethylamine in the dioxane medium. Anticancer screening of the synthesized thiazoles was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
(33 reference statements)
2
34
0
5
Order By: Relevance
“…were synthetized by reaction of 2-amino-5-R-benzyl-1,3-thiazoles with acid chlorides in the presence of triethylamine in dioxane medium at the Chemistry Faculty of Ivan Franko National University of Lviv, Ukraine as previously described [5,8]. Stock solutions of the tested compounds were prepared in dimethyl sulfoxide (DMSO, Sigma-Aldrich, St. Louis, USA).…”
Section: Compounds Thiazole Derivatives Bf1 and Pp2mentioning
confidence: 99%
See 2 more Smart Citations
“…were synthetized by reaction of 2-amino-5-R-benzyl-1,3-thiazoles with acid chlorides in the presence of triethylamine in dioxane medium at the Chemistry Faculty of Ivan Franko National University of Lviv, Ukraine as previously described [5,8]. Stock solutions of the tested compounds were prepared in dimethyl sulfoxide (DMSO, Sigma-Aldrich, St. Louis, USA).…”
Section: Compounds Thiazole Derivatives Bf1 and Pp2mentioning
confidence: 99%
“…introduction Thiazole derivatives are attractive heterocycles for pharmaceutical and medicinal chemists who design new potent anticancer agents [1][2][3][4]. It was shown that two novel thiazole derivatives -N-(5-benzyl-1,3-thiazol-2-yl)-3,5-dimethyl-1-benzofuran-2-carboxamide (BF1) and 7-benzyl-8-methyl-2-propylpyrazolo[4,3-e]thiazolo [3,2-a] pyrimidin-4(2H)-one (PP2) [5] have a high cytotoxic effect toward various cancer cell lines, such as glioblastoma (U251 and T98G) and human myeloid leukemia (HL 60 and K562) [6,7]. These compounds also had low toxicity towards human kidney cells (HEK 293) and human keratinocytes (HaCaT line) [5,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of our study was to test the cytotoxic effects in vitro of seven novel pyrazolothiazolopyrimidine derivatives that target several mammalian tumor cell lines and for comparison, pseudo-normal cell lines. The stock solution of tested compounds (10 mM) was prepared in dimethyl sulfoxide (DMSO, Sigma-Aldrich, St. Louis, MO, USA), and before adding to the cells, further solutions were prepared using culture medium [25]. Doxorubicin (Dox, Teva, Haarlem, the Netherlands) was used as a positive control.…”
Section: Abstract: Pyrazolothiazolopyrimidines Doxorubicin Amentioning
confidence: 99%
“…New thiazole derivative, namely N(5benzyl1,3thiazol2yl)3,5dimethyl1benzofuran-2-carboxamide (here noted as compound 1) demonstrated a toxicity against human glioblastoma U251 cells (IC 50 = 9.8±0.82 µM) and human melanoma WM793 cells (IC 50 = 7.2±0.48 µM) [6], while 2,8dimethyl7(3trifluoromethylbenzyl)pyra zolo [4,3e]thiazolo [3,2a]pyrimidin4one (here noted as compound 2) demonstrated a toxicity against human leukemia cells of HL60 (IC 50 was was 0.09±0.008 µM), against Jurkat and K562 lines (IC 50 was approximately 1 µM) [7]. IC 50 of compounds 1 and 2 for pseudo-normal cells was 3.2-30 µM [6,7]. Besides, it was shown that the compound 1 induced apoptosis and DNA damage, affected a transition of G2/M phase of cell cycle in human glioblastoma U251 cells [8, accepted].…”
Section: Introductionmentioning
confidence: 99%